Theodori Metochitae Carmina - Theodorus, Metochita (Corpus Christianorum / Series Graeca, 2015)
"The twenty Poems of Theodore Metochites (ca. 1270-1332) constitute a unique corpus of approximately 10.000 verses composed in the traditional Homeric hexameter. Metochites did not use the most common iambic verse, but chose to commemorate his deeds and immortalize his thoughts and experiences in the heroic Homeric verse. At the same time he took advantage of the poetic works of Gregory of Nazianzus, who exercised a considerable influence upon his language and his general attitude towards his fellow men and his social environment."--